Optimasi Pembentukan Bioflok Dari Skeletonema sp., Nitzschia sp. Dan Bakteri Probiotik Melalui Variasi pH Secara In Vitro - Malle, Asnady Ibrahim (Fakultas MIPA UNM, 2018)
Abstract. Bioflok is a microbial community consisting of bacteria, protozoa and zooplankton, as a shrimp feed supplement containing amino acids methionin, vitamins, minerals and enzymes that can help the process of digestion of feed on shrimp. Bioflux is a suspension contained in water consisting of microalgae, and bacteria that are potentially developed in the field of aquaculture that is as natural food because of high protein content as well as an alternative solution to the problem of cultivation waste. This study aims to find out how optimization of biofloc formation from Skeletonema sp., Nitzschia sp. and probiotic bacteria through the optimum salinity level used on the Walne medium. This research was conducted at Biology Laboratory of Makassar State University. This research was an experimental research using Completely Randomized Design (RAL) consisting of 5 treatments and 3 replications, ie treatment with pH 9, treatment with pH 8,5, treatment with pH 8, treatment with pH 7,5, treatment with pH 7 , pH 6.5 treatment, pH 6 treatment, and pH 5 treatment, on Walne medium using a combination of inoculant Skeletonema sp., Nitzschia sp. and probiotic bacteria. Parameters observed were biomass (dry weight) floc, floc volume, floc activity, temperature, pH, light intensity, and aeration rate. Data were analyzed using Analysis of Variance (ANOVA) and continued by Duncan test (Î± 0,05). The results showed that the treatment with pH 6.5 was the optimum salinity for biofloc formation shown by the highest floc biomass, the highest floc volume, and the highest floc activity with the floc volume indicator 0.01278 ml, dry weight (biomass) 0.00733 g / ml and floc activity 83.45 ml.Keywords: biofloc, ph, skeletonema sp., nitzschia sp., probiotic bacteria.Â